The BMI-Glucose Connection: Investigating the Association between Body Weight and Blood Sugar Levels (IAHS Medical Journal, 2024)
Background: Obesity is the most important modifiable risk factor in the pathogenesis of type-2 diabetes reported in most cross-sectional studies. The aim of the study is to examine the association between Body Mass Index (BMI) and blood sugar levels in a population sample.Materials and methods: An observational study was conducted on pregnant women with a positive family history of diabetes mellitus visiting in the Outpatient Department of Khulna City Medical Hospital from September 2022 to March 2023 to investigate the relationship between BMI and glucose level.Results: The study categorized 67 pregnant women based on their BMI, with respondents having a BMI of over 30 kg/m2 have a higher risk of high blood glucose levels. The study found that higher BMI categories are associated with an increased risk of having elevated 2-hour post-glucose blood sugar levels, indicating a potential link between BMI and glucose metabolism. The results suggest that maternal obesity may increase the prevalence of Gestational Diabetes Mellitus (GDM) which is consistent with the global trend of increased GDM prevalence along with the rise in obesity.Conclusion: The study concludes that BMI is a significant predictor of glucose metabolism in pregnant women with a positive family history of diabetes mellitus. Effective interventions to control maternal obesity may reduce the incidence of GDMIAHS Medical Journal Vol 6(1), June 2023; 47-49